Replacement Times of a Spectrum of Elements in the North Atlantic Based on Thorium Supply. Issue 9 (6th September 2018) - Hayes, Christopher T.; Anderson, Robert F.; Cheng, Hai; Conway, Tim M.; Edwards, R. Lawrence; Fleisher, Martin Q.; Ho, Peng; Huang, Kuo‐Fang; John, Seth G.; Landing, William M.; Little, Susan H.; Lu, Yanbin; et al.
Abstract: The measurable supply of 232 Th to the ocean can be used to derive the supply of other elements, which is more difficult to quantify directly. The measured inventory of an element divided by the derived supply yields a replacement time estimate, which in special circumstances is related to a residence time. As a proof of concept, Th‐based supply rates imply a range in the replacement times of the rare earth elements in the North Atlantic that is consistent with the chemical reactivity of rare earth elements related to their ionic charge density. Similar estimates of replacement times for the bioactive trace elements (Fe, Mn, Zn, Cd, Cu, and Co), ranging from <5 years to >50, 000 years, demonstrate the broad range of elemental reactivity in the ocean. Here we discuss how variations in source composition, fractional solubility ratios, or noncontinental sources, such as hydrothermal vents, lead to uncertainties in Th‐based replacement time estimates. We show that the constraints on oceanic replacement time provided by the Th‐based calculations are broadly applicable in predicting how elements are distributed in the ocean and for some elements, such as Fe, may inform us on how the carbon cycle may be impacted by trace element supply and removal. Key Points: Thorium‐232 supply rates produce reasonable ocean replacement times for the rare earth elements Iron residence time in the North Atlantic may be less than 6 years Thorium‐232 supply rates may provide an accurate basis for the supply of many other elements for constraining biogeochemical models